Technology and Tradition in Mesoamerica after the Spanish Invasion : Archaeological Perspectives - Alexander, Rani T., 1962- (Book collections on Project MUSE., 2019)
"This impressive collection features the work of archaeologists who systematically explore the material and social consequences of new technological systems introduced after the sixteenth-century Spanish invasion in Mesoamerica. It is the first collection to present case studies that show how both commonplace and capital-intensive technologies were intertwined with indigenous knowledge systems to reshape local, regional, and transoceanic ecologies, commodity chains, and political, social, and religious institutions across Mexico and Central America"--